Current Status And Problems Of The Sawmilling Industry In Thailand A Case Study In Bangkok Metropolitan Area - Dumrongthai, Pralong (1990)
Sawmilling industry in Thailand lack the technical information and data for improving the sawmill in goperation . Futhermore , severe log short age results to the forced shut -down / closure of several sawmills .In an effort to help solve these problems , this study was conducted to determine the current status and identify the problems faced by these sawmills . Based on the survey and field visits , the major problems included short age of raw material and flexible government policy.Most of the sawmills were very primitive and ill- equipped coupled with limited skilled lab our resulting to high production cost , low productivity rate and low recovery rate . There is also additional research and development that need to be carried out and advisory services to be provided to the sawmilling industry .The government must review its policies to wards promoting modern equipment and technology by giving supports through financing and training programs . Both government and private sectors must joint together in helping and upgrading the plight s o f the sawmills .